SYNBIOCHEM–a SynBio foundry for the biosynthesis and sustainable production of fine and speciality chemicals. (9th June 2016) - Carbonell, Pablo; Currin, Andrew; Dunstan, Mark; Fellows, Donal; Jervis, Adrian; Rattray, Nicholas J.W.; Robinson, Christopher J.; Swainston, Neil; Vinaixa, Maria; Williams, Alan; Yan, Cunyu; Barran, Perdita; et al.
Abstract : The Manchester Synthetic Biology Research Centre (SYNBIOCHEM) is a foundry for the biosynthesis and sustainable production of fine and speciality chemicals. The Centre's integrated technology platforms provide a unique capability to facilitate predictable engineering of microbial bio-factories for chemicals production. An overview of these capabilities is described.